Method for reversibly crosslinking compositions
By introducing BiTEMPS methacrylate and free radical initiator into ethylene polymers, a dynamic crosslinked ethylene polymer is solved, and the problem that crosslinked ethylene polymers cannot be processed and recycled is achieved, the reprocessability and recyclability of the material are improved, and the sustainability of the material is improved.
Patent Information
- Application Number
- CN202380052355.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-07-15
- Filing Date
- 2023-07-14
- Publication Date
- 2025-02-25
AI Technical Summary
Crosslinked ethylene polymers cannot be processed and/or recycled due to the presence of a permanent crosslinking network, resulting in environmental and sustainability problems.
A crosslinkable polymer composition is provided, including polar ethylene polymer, free radical initiator and 2,2,6,6-tetramethyl-4-piperidinyl methacrylate disulfide (BiTEMPS methacrylate), and mix at high temperature to form BiTEMPS methacrylate grafted ethylene polymer to achieve dynamic crosslinking.
Through dynamic crosslinking, the reprocessability and recyclability of ethylene polymers are achieved, which reduces environmental pollution and resource waste and improves the sustainability of materials.
Smart Images

Figure BDA0005231273930000121 
Figure BDA0005231273930000131 
Figure BDA0005231273930000151
Abstract
Description
Background Art
[0001] Crosslinked olefin polymers, particularly crosslinked ethylene polymers, are well known for their excellent mechanical properties, high thermal stability, and outstanding chemical resistance in numerous applications. Unfortunately, crosslinked ethylene polymers, also known as thermoset polymers, cannot be reprocessed and / or recycled due to the presence of a permanent crosslinking network within the ethylene polymer. Thus, the use of crosslinked ethylene polymers brings with it attendant environmental and sustainability issues.
[0002] The ability to reprocess and / or recycle crosslinked ethylene polymers has been a long-standing challenge. Accordingly, the art recognizes a need for crosslinked olefin polymers (and particularly crosslinked ethylene polymers) that can be reprocessed and / or recycled. Summary of the invention
[0003] The present disclosure provides a method. In one embodiment, the method includes providing a crosslinkable polymer composition. The crosslinkable polymer composition comprises (i) a (polar) ethylene polymer having a melting temperature Tm, (ii) a free radical initiator having a decomposition temperature Tm, 分解 , (iii) 2,2,6,6-tetramethyl-4-piperidinyl methacrylate disulfide (BiTEMPS methacrylate), and optional additives. The method comprises mixing the crosslinkable polymer composition in a mixing device at a temperature greater than or equal to the decomposition temperature of the peroxide and forming a BiTEMPS methacrylate-grafted (polar) vinyl polymer (BIT-g-pPE).
[0004] definition
[0005] All references to the Periodic Table of the Elements herein shall refer to the Periodic Table of the Elements published and copyrighted by CRC Press, Inc. in 2003. Furthermore, any reference to one or more groups shall be to the one or more groups reflected in such Periodic Table of the Elements using the IUPAC system for numbering groups. Unless stated to the contrary, implied by the context, or customary in the art, all parts and percentages are by weight. For purposes of U.S. patent practice, any patent, patent application, or publication referred to herein is incorporated herein by reference in its entirety (or its equivalent U.S. version is so incorporated by reference).
[0006] The numerical range disclosed herein includes all values from the lower limit to the upper limit and including the lower limit and the upper limit. For a range containing clear values (e.g., a range of 1 or 2, or 3 to 5, or 6, or 7), any sub-range between any two clear values is included (e.g., the above range 1 to 7 includes 1 to 2; 2 to 6; 5 to 7; 3 to 7; 5 to 6; etc.).
[0007] Unless stated to the contrary, implicit from the context, or customary in the art, all parts and percentages are by weight and all test methods are current as of the filing date of this disclosure.
[0008] As used herein, the term "composition" refers to a mixture that includes the materials of the composition, as well as reaction products and decomposition products formed from the materials of the composition.
[0009] The terms "comprising," "including," "having," and their derivatives are not intended to exclude the presence of any additional components, steps, or procedures, whether or not specifically disclosed. For the avoidance of any doubt, all compositions claimed through use of the term "comprising" may include any additional additives, adjuvants, or compounds, whether polymeric or otherwise, unless stated to the contrary. In contrast, the term "consisting essentially of excludes from the scope of any subsequent listing any other components, steps, or procedures, except those that are not essential to operability. The term "consisting of excludes any component, step, or procedure not specifically recited or listed.
[0010] "Ethylene polymers" are polymers containing more than 50 mol% of polymerized ethylene monomers (based on the total amount of polymerizable monomers) and optionally may contain at least one comonomer. Ethylene polymers include ethylene homopolymers and ethylene copolymers (meaning units derived from ethylene and one or more comonomers). The terms "ethylene polymers" and "polyethylene" are used interchangeably. Non-limiting examples of ethylene polymers (polyethylene) include low density polyethylene (LDPE) and linear polyethylene. Non-limiting examples of linear polyethylene include linear low density polyethylene (LLDPE), ultra low density polyethylene (ULDPE), very low density polyethylene (VLDPE), ethylene / alpha-olefin multi-block copolymers (also known as olefin block copolymers (OBC)), substantially linear or linear plastomers / elastomers, and high density polyethylene (HDPE). Generally speaking, polyethylene can be produced in a gas phase fluidized bed reactor, a liquid phase slurry reactor or a liquid phase solution reactor using a heterogeneous catalyst system (such as a Ziegler-Natta catalyst), a homogeneous catalyst system comprising a Group 4 transition metal and a ligand structure (such as a metallocene, a non-metallocene metal center, a heteroaryl, an isovalent aryloxy ether, a phosphinimine, etc.). Combinations of heterogeneous and / or homogeneous catalysts can also be used in a single reactor or multiple reactor configurations.
[0011] An "ethylene plastomer / elastomer" is a substantially linear or linear ethylene / α-olefin interpolymer containing a homogeneous distribution of short chain branches, the ethylene / α-olefin interpolymer comprising units derived from ethylene and units derived from at least one C3-C 10 The ethylene plastomers / elastomers have a density of 0.854 g / cc to 0.920 g / cc. Non-limiting examples of ethylene plastomers / elastomers include AFFINITY TM Polyolefin plastomers and ENGAGE TM Polyolefin elastomer (available from The Dow Chemical Company), EXACT TM Plastomers (available from ExxonMobil Chemical), Tafmer TM α-olefin copolymer (available from Mitsui), Solumer TM Polyolefin Elastomers and Supreme TM Polyolefin elastomer (available from SK Chemicals Co.) and Lucene TM Polyolefin elastomer (available from LG Chem Ltd.).
[0012] "High density polyethylene" (or "HDPE") is a homopolymer of ethylene or ethylene with at least one C4-C 10 The HDPE may be a unimodal copolymer or a multimodal copolymer. A "unimodal ethylene copolymer" is an ethylene / α-olefin copolymer having one distinct peak in a gel permeation chromatography (GPC) showing a molecular weight distribution. 10 α-olefin copolymers. "Multimodal ethylene copolymers" are ethylene / C4-C6 copolymers having at least two distinct peaks in a GPC graph showing molecular weight distribution. 10 α-olefin copolymers. Multimodal includes copolymers with two peaks (bimodal) and copolymers with more than two peaks. Non-limiting examples of HDPE include DOW TM High-density polyethylene (HDPE) resin (available from The Dow Chemical Company), ELITE TMEnhanced polyethylene resin (available from The Dow Chemical Company), CONTINUUM TM Bimodal polyethylene resin (available from The Dow Chemical Company), LUPOLEN TM (available from LyondellBasell) and HDPE products from Borealis, Ineos and ExxonMobil.
[0013] As used herein, the term "linear low density polyethylene" (or "LLDPE") refers to a linear ethylene / α-olefin copolymer containing a heterogeneous distribution of short chain branches, the copolymer comprising units derived from ethylene and units derived from at least one C3-C 10 Units of α-olefins or C4-C8 α-olefin comonomers. LLDPE is characterized by minimal long chain branching (if any) compared to conventional LDPE. LLDPE has a density of 0.910 g / cc to less than 0.940 g / cc. Non-limiting examples of LLDPE include TUFLIN TM Linear low density polyethylene resin (available from The Dow Chemical Company), DOWLEX TM Polyethylene resin (available from The Dow Chemical Company) and MARLEX TM Polyethylene (available from Chevron Phillips).
[0014] The term "low density polyethylene" (or "LDPE") may also be referred to as "high pressure ethylene polymer" or "highly branched polyethylene" and is an ethylene homopolymer and is typically produced by high pressure free radical polymerization ((≥100 MPa (e.g., 100 MPa to 400 MPa), tubular reactor or autoclave reactor with a free radical initiator). The density of LDPE resins is typically in the range of 0.915 g / cc to less than 0.940 g / cc. LDPE is distinct from LLDPE.
[0015] As used herein, "olefin polymer" or "polyolefin" is a polymer containing more than 50 mole % polymerized olefin monomer (based on the total amount of polymerizable monomers) and optionally may contain at least one comonomer. Non-limiting examples of olefin polymers include ethylene-based polymers and propylene-based polymers.
[0016] "Polymer" is a compound prepared by polymerizing monomers of the same or different types, which provide multiple and / or repeated "units" or "monomer units" constituting the polymer in a polymerized form. Therefore, the general term polymer covers the term homopolymer, which is usually used to refer to polymers prepared from only one type of monomer, and the term copolymer, which is usually used to refer to polymers prepared from at least two types of monomers. It also covers all forms of copolymers, such as random copolymers, block copolymers, etc. The terms "ethylene / α-olefin polymer" and "propylene / α-olefin polymer" represent copolymers prepared by polymerizing ethylene or propylene and one or more other polymerizable α-olefin monomers, respectively, as described above. It should be noted that although polymers are generally referred to as "made of" one or more specified monomers, "based on" a specified monomer or monomer type, "containing" a specified monomer content, etc., in this context, the term "monomer" should be understood to refer to the polymerized residue of the specified monomer rather than unpolymerized substances. In general, polymers are referred to herein as "units" based on the polymerized form of the corresponding monomers.
[0017] Test Method
[0018] Compression molded samples Form at 180°C and 10 MPa molding pressure for 5 minutes and then quench between cooling platens (15-20°C) for 2 minutes, or as otherwise described herein.
[0019] density Measured according to ASTM D792, where results are reported in g / cc at 25°C.
[0020] Dynamic Mechanical Analysis (DMA). DMA experiments were performed using a TA Instruments RSA-G2 solid analyzer to measure the storage modulus (G'), loss modulus (G"), and damping ratio (tan δ) of the networks as a function of temperature and recovery under a nitrogen atmosphere. The DMA was run in tension mode with a frequency of 1 Hz and an oscillating strain of 0.03%. Data were collected from room temperature to 160°C at a heating rate of 3°C / min.
[0021] Measured using ASTM D648 method Heat distortion temperature (HDT) The temperatures at which the samples deformed under loads of 0.455 MPa and 1.82 MPa are reported.
[0022] Melt Index (MI or I2) (for ethylene polymers) is measured according to ASTM D 1238, Condition 190°C / 2.16 kg, where the results are reported in grams per 10 minutes (g / 10 min). 21Measured according to ASTM D 1238, Condition 190°C / 21.6 kg, where the results are reported in grams per 10 minutes (g / 10 min).
[0023] Rheological analysis Use rubber processing analyzer (RPA) to carry out.Use rotorless oscillating shear rheometer AlphaTechnologies RPA 2000 instrument, according to ASTM D6204, measure the rheology of composition under the following test conditions and exceptions.Sample is placed between two polyester films for analysis.Rheology is monitored at 180 ℃, 1.0rad / s, 7% strain for 60 minutes during initial timing test.Record the elastic torque S' at the end of 60 minutes (min) crosslinking step.After 60 minutes at 160 ℃, immediately at 180 ℃, 7% strain, the same sample is subjected to a frequency sweep of 0.1rad / s to 300rad / s, then at 190 ℃, 7% strain, a frequency sweep of 0.1rad / s to 300rad / s, and then at 230 ℃, 7% strain, a frequency sweep of 0.1rad / s to 300rad / s.Record the dynamic complex viscosity, n* and tanδ of each frequency sweep. In ASTM D6204, a frequency sweep is performed on unvulcanized rubber before the curing step. In this case, a frequency sweep is performed at 180°C after the initial crosslinking step to evaluate the reversibility of the crosslinking. The viscosity-temperature reprocessing ratio (or "VRR") is defined as follows:
[0024] VRR is the ratio of n* at 0.1 rad / s and 180°C to n* at 0.1 rad / s and 230°C.
[0025] Thermomechanical analysis (Penetration Temperature) was conducted on 30 mm diameter x 3.3 mm thick compression molded discs, formed at 180°C and 10 MPa molding pressure for 5 minutes, and then air quenched. The instrument used was a TA Instruments TMA400, a thermomechanical analyzer. In the test, a 1.5 mm probe was applied to the surface of the sample disc with a force of 1 N. The temperature was increased from 25°C at 5°C / min. Probe penetration was measured as a function of temperature. The experiment ended when the probe penetrated into the sample at 1000 mm (1 mm).
[0026] Vicat softening point Measured using ASTM D 1525. Report the temperature at which a flat-tip needle penetrates the sample to 1 mm thickness when loaded with 10 N. DETAILED DESCRIPTION
[0027] The present disclosure provides a method. In one embodiment, the method includes providing a crosslinkable polymer composition. The crosslinkable polymer composition comprises (i) a (polar) ethylene polymer having a melting temperature Tm, (ii) a free radical initiator having a decomposition temperature Tm, 分解 , (iii) 2,2,6,6-tetramethyl-4-piperidinyl methacrylate disulfide (BiTEMPS methacrylate), and optional additives. The method comprises mixing the crosslinkable polymer composition in a mixing device at a temperature greater than or equal to the decomposition temperature of the peroxide and forming a BiTEMPS methacrylate-grafted (polar) vinyl polymer (BIT-g-pPE).
[0028] A. (Polar) Ethylene Polymers
[0029] The blend components include (polar) ethylene polymers. As used herein, "(polar) ethylene polymers" are (i) polar ethylene polymers, (ii) ethylene polymers, or (iii) a combination of (i) and (ii). As used herein, "polar ethylene polymers" are ethylene polymers consisting of (i) ethylene monomers, (ii) comonomers containing heteroatoms, and (iii) optional terionomers (which may or may not contain heteroatoms). In other words, polar ethylene polymers are not hydrocarbons. The melt index (MI) of polar ethylene polymers is 0.1 g / 10min to 100 g / 10min, or 1 g / 10min to 100 g / 10min, or 1 g / 10min to 50 g / 10min, or 1 g / 10min to 25 g / 10min, or 1 g / 10min to 10 g / 10min, or 1 g / 10min to 5 g / 10min. Non-limiting examples of comonomers having heteroatoms include carbon monoxide, carboxylic acids, esters, alkyl acrylates having 1 to 30 carbon atoms, methacrylates having 1 to 30 carbon atoms, vinyl siloxanes having 1 to 16 carbon atoms, and halogens. Non-limiting examples of suitable polar vinyl polymers include ethylene / carboxylic acid copolymers and ionomers partially neutralized with metal salts derived therefrom, ethylene / acrylic acid copolymers (EAA), ethylene / methacrylic acid copolymers (EMAA), ethylene / vinyl (trimethoxy) silane copolymers (EVTMS), ethylene / vinyl acetate copolymers (EVA), ethylene / methyl acrylate (EMA), ethylene / ethyl acrylate copolymers (EEA), ethylene / butyl acrylate copolymers (EBA), ethylene / carbon monoxide (ECO), ethylene / glycidyl methacrylate (E / GMA), ethylene / methyl methacrylate copolymers, ethylene / butyl methacrylate copolymers, ethylene / octadecyl acrylate copolymers, ethylene / octadecyl methacrylate copolymers, ethylene / octyl acrylate copolymers, ethylene / 2-ethylhexyl acrylate copolymers, ethylene / dodecyl acrylate copolymers, polyvinyl dichloride (PVCD), ethylene / maleic anhydride copolymers (EMAH), polyvinyl chloride (PVC), and combinations thereof.Additional non-limiting examples of terpolymers include ethylene / carboxylic acid / acrylate terpolymers and partially neutralized ionomers with metal salts derived therefrom, ethylene / methyl acrylate / vinyl (trimethoxy) silane terpolymers (EMAVTMS), ethylene / ethyl acrylate / vinyl (trimethoxy) silane terpolymers (EEAVTMS), ethylene / butyl acrylate / vinyl (trimethoxy) silane terpolymers (EBAVTMS), ethylene / methyl acrylate / glycidyl methacrylate (EMAGMA), ethylene / butyl acrylate / glycidyl methacrylate (EBAGMA), ethylene / vinyl acetate / maleic anhydride terpolymers (EEAMAH), ethylene ethyl acrylate / maleic anhydride (EEAMAH) terpolymers, and combinations thereof.
[0030] In one embodiment, the polar vinyl polymer is an ethylene / vinyl acetate copolymer.
[0031] The (polar) ethylene polymer may be an ethylene polymer. As used herein, "ethylene polymer" is a hydrocarbon and is therefore different from a polar ethylene polymer containing heteroatoms. The ethylene polymer may be an ethylene homopolymer, an ethylene / α-olefin interpolymer or an ethylene / C4-C 20 Alpha-olefin copolymers. In embodiments herein, ethylenes include more than 50% by weight of units derived from ethylene and less than 30% by weight of units derived from one or more alpha-olefin comonomers (based on the total amount of polymerizable monomers). All individual values and subranges of units derived from ethylene greater than 50% by weight and less than 30% by weight of units derived from one or more alpha-olefin comonomers. Suitable alpha-olefin comonomers generally have no more than 20 carbon atoms. For example, alpha-olefin comonomers may have 3 to 10 carbon atoms or 3 to 8 carbon atoms. Exemplary alpha-olefin comonomers include, but are not limited to, propylene, 1-butene, 1-pentene, 1-hexene, 1-heptene, 1-octene, 1-nonene, 1-decene and 4-methyl-1-pentene. The one or more α-olefin comonomers may, for example, be selected from the group consisting of propylene, 1-butene, 1-hexene, and 1-octene; or in the alternative, selected from the group consisting of 1-butene, 1-hexene, and 1-octene; or in the alternative, selected from the group consisting of 1-hexene and 1-octene. In some embodiments, the ethylene-based polymer comprises greater than 0 wt % and less than 30 wt % of units derived from one or more of 1-octene, 1-hexene, or 1-butene comonomers.
[0032] The melt index (MI) of the ethylene polymer is 0.1 g / 10min to 100 g / 10min, or 1 g / 10min, to 100 g / 10min, or 1 g / 10min to 50 g / 10min, or 1 g / 10min to 25 g / 10min, or 1 g / 10min to 10 g / 10min, or 1 g / 10min to 5 g / 10min. In embodiments herein, the density of the ethylene polymer is in the range of 0.854 g / cc to 0.925 g / cc. All individual values and subranges of 0.854 g / cc to 0.925 g / cc are included and disclosed herein. In some embodiments, the density of the ethylene composition may be 0.895 g / cc to 0.925 g / cc, 0.900 g / cc to 0.925 g / cc, 0.900 g / cc to 0.920 g / cc, 0.900 g / cc to 0.915 g / cc, 0.900 g / cc to 0.912 g / cc, 0.900 g / cc to 0.911 g / cc, or 0.900 g / cc to 0.910 g / cc. In further specific embodiments, the density of the ethylene polymer composition may be 0.875 g / cc to 0.925 g / cc, 0.890 g / cc to 0.925 g / cc, 0.900 g / cc to 0.925 g / cc, 0.903 g / cc to 0.925 g / cc, or 0.905 g / cc to 0.925 g / cc. Density can be measured according to ASTM D792.
[0033] Non-limiting examples of suitable ethylene-based polymers include ethylene / α-olefin interpolymers, high density polyethylene (HDPE), linear low density polyethylene (LLDPE), low density polyethylene (LDPE), and combinations thereof.
[0034] In one embodiment, the ethylene / α-olefin interpolymer is an ethylene / C4-C8 α-olefin copolymer having one, some, or all of the following characteristics:
[0035] (i) octene comonomer; and / or
[0036] (ii) a density of 0.860 g / cc to 0.925 g / cc, or 0.880 g / cc to 0.920 g / cc, or 0.899 g / cc to 0.915 g / cc, or 0.899 g / cc to 0.910 g / cc; and / or
[0037] (iii) a melt index of 0.5 g / 10 min to 100 g / 10 min, or 1 g / 10 min to 30 g / 10 min, or 2 g / 10 min to 20 g / 10 min. Non-limiting examples of suitable ethylene / C4-C8 α-olefin copolymers include ENGAGE TM 8450POE、ENGAGE TM 8402POE、ENGAGE TM 8401POE、ELITE TM 5815 reinforced polyethylene resin, ELITE TM 5220 reinforced polyethylene resin or their blends.
[0038] In one embodiment, the ethylene polymer is an ethylene / α-olefin multi-block copolymer. The term "ethylene / α-olefin multi-block copolymer" refers to an ethylene / C3-C8α-olefin multi-block copolymer composed of ethylene and a copolymerizable C3-C8α-olefin comonomer or C4-C8α-olefin comonomer (and optional additives) in polymerized form, and the polymer is characterized in that multiple blocks or segments of two polymerized monomer units are different in chemical or physical properties, and the blocks are connected (or covalently bonded) in a linear manner, i.e., a polymer containing chemically distinguishable units connected end-to-end relative to the polymerized olefinic functionality. Ethylene / α-olefin multi-block copolymers include block copolymers with two blocks (diblocks) and more than two blocks (multi-blocks). C3-C8α-olefins are selected from propylene, butene, hexene and octene. Ethylene / α-olefin multi-block copolymers do not contain or otherwise do not contain styrene (i.e., do not contain styrene), and / or vinyl aromatic monomers, and / or conjugated dienes. When referring to the amount of "ethylene" or "comonomer" in a copolymer, it is understood that this refers to polymerized units thereof. In some embodiments, the ethylene / α-olefin multi-block copolymer may be represented by the formula: (AB) n; wherein n is at least 1, preferably an integer greater than 1, such as 2, 3, 4, 5, 10, 15, 20, 30, 40, 50, 60, 70, 80, 90, 100 or more, "A" represents a hard block or segment and "B" represents a soft block or segment. Preferably, A and B are connected or covalently bonded in a substantially linear manner, or in a linear manner, relative to a substantially branched or substantially star-shaped manner. In other embodiments, the A blocks and B blocks are randomly distributed along the polymer chain. In other words, the block copolymer generally does not have the following structure: AAA-AA-BBB-BB. In one embodiment, the ethylene / α-olefin multi-block copolymer does not have a third type of block, which comprises one or more different comonomers. In another embodiment, block A and block B each have monomers or comonomers that are substantially randomly distributed within the block. In other words, neither block A nor block B comprises two or more subsegments (or subblocks) of different compositions, such as an end segment having a substantially different composition than the remainder of the block.
[0039] In one embodiment, ethylene accounts for the majority of the mole fraction of the entire ethylene / α-olefin multi-block copolymer, i.e., ethylene accounts for at least 50% by weight of the entire ethylene / α-olefin multi-block copolymer. More preferably, ethylene accounts for at least 60% by weight, at least 70% by weight, or at least 80% by weight, and the substantial remainder of the entire ethylene / α-olefin multi-block copolymer comprises C3-C8 α-olefin comonomers or C4-C8 α-olefin comonomers.
[0040] In one embodiment, the ethylene / α-olefin multi-block copolymer contains from 50 wt% to 90 wt% ethylene, or from 60 wt% to 85 wt% ethylene, or from 65 wt% to 80 wt% ethylene.
[0041] Ethylene / alpha-olefin multi-block copolymers include various amounts of "hard" segments and "soft" segments. "Hard" segments are blocks of polymerized units, wherein based on the weight of the polymer, ethylene is present in an amount greater than 90 wt %, or 95 wt %, or greater than 95 wt %, or greater than 98 wt %, up to 100 wt %. In other words, by the weight of the polymer, the comonomer content (except the monomer content of ethylene) in the hard segments is less than 10 wt %, or 5 wt %, or less than 5 wt %, or less than 2 wt %, and can be as low as zero. In some embodiments, the hard segments include all or substantially all units derived from ethylene. "Soft" segments are blocks of polymerized units, in which, by the weight of the polymer, the comonomer content (the content of monomers other than ethylene) is greater than 5 wt %, or greater than 8 wt %, greater than 10 wt %, or greater than 15 wt %. In one embodiment, the comonomer content in the soft segments is greater than 20 wt%, greater than 25 wt%, greater than 30 wt%, greater than 35 wt%, greater than 40 wt%, greater than 45 wt%, greater than 50 wt%, or greater than 60 wt% and can be as high as 100 wt%.
[0042] The soft segment can be present in ethylene / alpha-olefin multi-block copolymers from 1% to 99% by weight of the total weight of the ethylene / alpha-olefin multi-block copolymer, or from 5% to 95% by weight, 10% to 90% by weight, 15% to 85% by weight, 20% to 80% by weight, 25% to 75% by weight, 30% to 70% by weight, 35% to 65% by weight, 40% to 60% by weight, or 45% to 55% by weight of the total weight of the ethylene / alpha-olefin multi-block copolymer. On the contrary, the hard segment can be present in a similar range. The soft segment weight percentage and the hard segment weight percentage can be calculated based on the data obtained from DSC or NMR. Such methods and calculations are disclosed in, for example, USP 7,608,668, entitled "Ethylene / α-Olefin Block Inter-Polymers", filed on March 15, 2006 in the name of Colin L.P. Shan, Lonnie Hazlitt et al. and assigned to Dow Global Technologies Inc., the disclosure of which is incorporated herein by reference in its entirety. Specifically, the hard segment weight percentage and the soft segment weight percentage and the comonomer content can be determined as described in columns 57 to 63 of USP 7,608,668.
[0043] In addition, the ethylene / α-olefin multi-block copolymer has a PDI (or Mw / Mn) that fits the Schultz-Flory distribution rather than the Poisson distribution. The ethylene / α-olefin multi-block copolymer of the present invention has both a polydisperse block distribution and a polydisperse distribution of block sizes. This results in the formation of a polymer product with improved and distinguishable physical properties. The theoretical benefits of a polydisperse block distribution have been previously described in Potemkin, Physical Review E( Physical Review ) (1998) 57(6), pp. 6902-6912 and Dobrynin, Journal of Chemical Physics ( J.Chem.Phvs.)》 Modeled and discussed in (1997) 107(21), pp. 9234-9238.
[0044] In one embodiment, the ethylene / α-olefin multi-block copolymers of the present invention have a most probable distribution of block lengths.
[0045] In one embodiment, the ethylene / α-olefin multi-block copolymer is an ethylene / 1-octene multi-block copolymer (consisting only of ethylene and octene comonomers) and has one, some, or all of the following properties:
[0046] (i) Mw / Mn is from 1.7, or 1.8 to 2.2, or 2.5, or 3.5; and / or
[0047] (ii) a density of 0.860 g / cc, or 0.865 g / cc to 0.870 g / cc, or 0.877 g / cc, or 0.880 g / cc; and / or
[0048] (iii) a melting point Tm of 115°C, or 118°C, or 119°C, or 120°C to 120°C, or 123°C, or 125°C; and / or
[0049] (iv) a melt index (MI) of 0.1 g / 10 min, or 0.5 g / 10 min to 1.0 g / 10 min, or 2.0 g / 10 min, or 5 g / 10 min, or 10 g / 10 min; and / or
[0050] (v) 50 to 85 weight percent soft segments and 50 to 15 weight percent hard segments (based on the total weight of the ethylene / octene multi-block copolymer); and / or
[0051] (vi) 10 mol%, or 13 mol%, or 14 mol%, or 15 mol% to 16 mol%, or 17 mol%, or 18 mol%, or 19 mol%, or 20 mol% octene in the soft segments; and / or
[0052] (vii) 0.5 mol%, 1.0 mol%, 2.0 mol%, or 3.0 mol% in the hard segment
[0053] to 4.0 mol%, or 5 mol%, or 6 mol%, or 7 mol%, or 9 mol% of octene; and / or
[0054] (viii) At 21°C, at 300% min, as measured according to ASTM D 1708 -1 50%, or 60% to 70%, or 80%, or 90% elastic recovery (Re) at deformation rate; and / or
[0055] (ix) Polydispersity distribution of blocks and polydispersity distribution of block sizes (hereinafter referred to as multi-block copolymer properties (i) to (ix)).
[0056] In one embodiment, the ethylene / α-olefin multi-block copolymer is an ethylene / octene multi-block copolymer. The ethylene / octene multi-block copolymer is marketed under the trade name INFUSE TM Olefin block copolymers are commercially available from The Dow Chemical Company, Midland, Michigan, USA.
[0057] Ethylene / α-olefin multi-block copolymers can be produced via a chain shuttling process as described in USP 7,858,706, which is incorporated herein by reference. Specifically, suitable chain shuttling agents and related information are listed in column 16, line 39 to column 19, line 44. Suitable catalysts are described in column 19, line 45 to column 46, line 19 and suitable co-catalysts are described in column 46, line 20 to column 51, line 28. The process is described throughout the literature, but particularly in column 51, line 29 to column 54, line 56. The process is also described, for example, in the following: USP 7,608,668; USP 7,893,166; and USP 7,947,793.
[0058] B. Free Radical Initiators
[0059] The crosslinkable composition comprises a free radical initiator. In one embodiment, the free radical initiator is an organic peroxide. Non-limiting examples of suitable organic peroxides include bis(1,1-dimethylethyl)peroxide; bis(1,1-dimethylpropyl)peroxide; 2,5-dimethyl-2,5-bis(1,1-dimethylethylperoxy)hexane; 2,5-dimethyl-2,5-bis(1,1-dimethylethylperoxy)hexyne; 4,4-bis(1,1-dimethylethylperoxy)pentanoic acid; butyl ester; 1,1-bis(1,1-dimethylethylperoxy)-3,3,5-trimethylcyclohexane; benzoyl peroxide; tert-butyl peroxybenzoate; di-tert-amyl peroxide ( "DTAP"); bis(α-tert-butylperoxyisopropyl)benzene ("BIPB"); isopropylcumyl tert-butyl peroxide; tert-butylcumyl peroxide; di-tert-butyl peroxide; 2,5-bis(tert-butylperoxy)-2,5-dimethylhexane; 2,5-bis(tert-butylperoxy)-2,5-dimethylhexyne-3,1,1-bis(tert-butylperoxy)-3,3,5-trimethylcyclohexane; isopropylcumylcumyl peroxide; butyl 4,4-di(tert-butylperoxy)valerate; di(isopropylcumyl) peroxide; diisopropylbenzene peroxide, and combinations thereof.
[0060] In one embodiment, the free radical initiator is dicumyl peroxide.
[0061] C. BiTEMPS methacrylate disulfide
[0062] The blend component comprises 2,2,6,6-tetramethyl-4-piperidinyl methacrylate disulfide, interchangeably referred to as "BiTEMPS methacrylate" or "BiTEMPS" or "BiT." BiTEMPS methacrylate disulfide has the following structure 1.
[0063] Structure 1
[0064]
[0065] D. Blend Components
[0066] In one embodiment, the crosslinkable polymer composition and / or the crosslinked composition comprises a blend component. Non-limiting examples of suitable blend components include polyolefins (e.g., polyethylene other than ethylene polymers crosslinked with BiTEMPS methacrylate and polypropylene), polymers (e.g., polystyrene, ABS, SBS, etc.), and combinations thereof. Non-limiting examples of suitable polyolefins include polyethylene; polypropylene; polybutene (e.g., polybutene-1); polypentene-1; polyhexene-1; polyoctene-1; polydecene-1; poly-3-methylbutene-1; poly-4-methylpentene-1; polyisoprene; polybutadiene; poly-1,5-hexadiene; interpolymers derived from olefins; interpolymers derived from olefins and other polymers such as polyvinyl chloride, polystyrene, polyurethane, etc.; and mixtures thereof.
[0067] E. Additives
[0068] The crosslinkable polymer composition and / or the crosslinked composition may contain one or more optional additives. Non-limiting examples of suitable additives include grafting initiators, crosslinking catalysts, blowing agents, blowing agent activators (e.g., zinc oxide, zinc stearate, etc.), auxiliary agents (e.g., triallyl cyanurate), plasticizers, processing oils, processing aids, carbon black, colorants or pigments, stability control agents, nucleating agents, fillers, antioxidants, acid scavengers, ultraviolet (UV) stabilizers, flame retardants, lubricants, processing aids, extrusion aids, and combinations thereof. When present, the total amount of the additive may be greater than 0% to 80%, or 0.001% to 70%, or 0.01% to 60%, or 0.1% to 50%, or 0.1% to 40%, or 0.1% to 20%, or 0.1% to 10%, or 0.1% to 5% of the total weight of the composition.
[0069] F. Mix
[0070] The components of the crosslinkable composition ((polar) vinyl polymer, peroxide and BiTEMPS) are mixed in a mixing device. In one embodiment, the crosslinkable polymer composition comprises:
[0071] 70 wt % to 98.5 wt %, or 77 wt % to 98.5 wt % of an ethylene polymer; 0.1 wt % to 10 wt %, or 0.1 wt % to 5 wt %, 0.1 wt % to 3.0 wt %, or 0.1 wt % to 1.5 wt %, or 0.5 wt % to 1.5 wt % of a free radical initiator which is an organic peroxide such as dicumyl peroxide; and
[0072] 1 wt % to 20 wt %, or 1 wt % to 15 wt %, or 2 wt % to 20 wt %, or 2 wt % to 10 wt % BiTEMPS methacrylate disulfide. It is understood that the aggregate of the vinyl polymer, free radical initiator, and BiTEMPS methacrylate disulfide (and optional additives) totals 100 wt % of the crosslinkable polymer composition.
[0073] The method comprises mixing the crosslinkable composition in a mixing device at a temperature greater than or equal to the decomposition temperature of the free radical initiator (peroxide) and forming a BiTEMPS methacrylate grafted (polar) vinyl polymer (BIT-g-pPE). BiT-g-pPE comprises a (polar) vinyl polymer ("PPe") grafted with BiTEMPS methacrylate (BiT). The BiT is side-grafted onto the (polar) vinyl polymer chain. The BiT forms a graft bond with the (polar) vinyl polymer, and the graft bond has the following structure 3:
[0074]
[0075] The term (and structure) "P" in the above Structure 3 refers to the chains of polymerized (polar) ethylene (and optional comonomers) of the (polar) ethylene polymer. The ethylene polymer of the crosslinked composition can be any ethylene polymer having a MI of 0.1 g / 10 min to 100 g / 10 min as previously disclosed herein.
[0076] In one embodiment, an extruder is used in the post-reactor step to produce BiT-g-pPE. The extruder can be a single screw extruder, a multi-screw extruder with positive and negative conveying screw elements, and a lobed kneading / mixing plate, paddle or block.
[0077] In one embodiment, the mixing comprises
[0078] (A) melt blending a (polar) ethylene-based polymer at a first temperature for a first process period;
[0079] (B) adding BiTEMPS and a free radical initiator to the melt blended ethylene polymer of step (A) during a second process period to form a reaction mixture;
[0080] (C) blending the reaction mixture at a second temperature for a third process period; and
[0081] (D) Formation of BiT-g-pPE.
[0082] The (polar) ethylene polymer is melt blended in a first period of time. In one embodiment, the first temperature of process step (A) is T of the (polar) ethylene polymer. mThe first temperature is sufficient to cause complete or substantially complete melting of the (polar) ethylene polymer.
[0083] In one embodiment, the first temperature is a temperature of 90°C to less than 160°C, or 95°C to 150°C, or 100°C to 140°C, or 110°C to 130°C. In a further embodiment, the first temperature is greater than or equal to the Tm of the (polar) ethylene polymer to less than the Tm of the free radical initiator. 分解 temperature.
[0084] In the second period, BiTEMPS and a free radical initiator are added and mixed into the molten (polar) ethylene polymer. In one embodiment, the first process period ends before the second process period begins.
[0085] During the third time period, the second temperature is sufficient to initiate (i.e., "start") the free radical initiator. In one embodiment, the second temperature in process step (C) is greater than or equal to the T of the free radical initiator. 分解 In further embodiments, the free radical initiator is a peroxide (such as dicumyl peroxide), and the second temperature is 160°C to less than 180°C, or 160°C to 179°C, or 160°C to 175°C, or 161°C to 173°C.
[0086] In one embodiment, steps (A) to (C) are carried out in an extruder. Alternatively, steps (A) to (C) are carried out in a batch mixing device (such as a Haake TM mixing device).
[0087] This method forms (D)BiT-g-pPE.
[0088] In one embodiment, the method includes collecting the BiT-g-pPE.The BiT-g-pPE can be collected or otherwise formed as a plurality of pellets, as one or more bags, or as a combination of pellets and bags.
[0089] In one embodiment, steps (A) to (C) are performed in an extruder. In another embodiment, steps (A) to (C) are performed in a mixture (such as a Haake TM mixture).
[0090] In one embodiment, the ethylene-based graft polymer is prepared by reactive extrusion. Reactive extrusion is understood by those skilled in the art, such as those described in M. Xanthos, Reactive Extrusion: Principles and Practice, Hanser Publishers, January 1, 1992, Technology & Engineering. In one embodiment, a co-rotating twin-screw extruder can be used. The L / D ratio of the extruder can be 36 to 60. All individual values and subranges are included and disclosed. For example, the L / D ratio of the extruder can be 44 to 60, 44 to 50, or 50 to 60. Twin screw extruders can be used in series to achieve an effective L / D ratio of 80 to 90. The diameter (D) of the extruder can be 30 mm to 200 mm.
[0091] The extruder can be operated at a production rate sufficient to produce greater than or equal to 2,000 lbs. grafted ethylene-based polymer / hour, or greater than or equal to 2,100 lbs. grafted ethylene-based polymer / hour, or greater than or equal to 2,200 lbs. grafted ethylene-based polymer / hour. One skilled in the art can convert the high rates to extruders of different sizes.
[0092] The screw speed may be 200 rpm to 900 rpm. The screw speed is adjusted based on the torque produced and the melt temperature. The barrel temperature in the reaction zone of the extruder may be between 160° C. and 250° C. At the inlet of the extruder, the temperature will be kept low (e.g., below 150° C.) to avoid premature melting. Near the end of the extruder, the temperature may be lowered to cool the melt.
[0093] G. Cross-linking
[0094] In one embodiment, the method comprises heating the BiT-g-pPE to a crosslinking temperature of 180°C to less than 199°C, forming the BiT-g-pPE into a preform at the crosslinking temperature; cooling the preform to below the crosslinking temperature; and forming a crosslinked article. In a further embodiment, the crosslinked article comprises (i) a (polar) ethylene polymer and a bond having structure 2 formed from 2,2,6,6-tetramethyl-4-piperidinyl methacrylate disulfide (BiTEMPS methacrylate). The crosslinked article contains a disulfide bond formed from BiTEMPS methacrylate by a crosslinking reaction, the disulfide bond having the following structure 2.
[0095] Structure 2
[0096]
[0097] The term (and structure) "P" in Structure 2 above refers to the chains of polymerized (polar) ethylene (and optional comonomers) of the (polar) ethylene polymer. The ethylene polymer of the crosslinked composition can be any ethylene polymer having a MI of 0.1 g / 10 min to 100 g / 10 min as previously disclosed herein.
[0098] In one embodiment, the forming step is a procedure selected from the group consisting of injection molding, extrusion molding, thermoforming, blow molding, overmolding, insert molding, blow molding, casting, tentering, compression molding, and combinations thereof.
[0099] Non-limiting examples of suitable articles for the crosslinked (polar) ethylene polymer compositions having bonds of Structure 2 formed from BiTEMPS methacrylate include elastic films; elastic fibers; soft-touch items such as toothbrush handles and appliance handles; pads and profiles; adhesives (including hot melt adhesives and pressure sensitive adhesives); footwear (including soles and shoe insoles); automotive interior parts and profiles; foam articles (both open-cell and closed-cell foams); impact modifiers for other thermoplastic polymers such as high-density polyethylene, isotactic polypropylene or other olefin polymers; coated fabrics; hoses; pipes; weatherstripping; lid linings; flooring; and combinations thereof.
[0100] H. Reprocessing
[0101] BiTEMPS methacrylate is a "dynamic crosslinker." The dynamic crosslinker BiTEMPS methacrylate enables the formation of a crosslinked network of ethylene polymers through disulfide bonds between chains of the ethylene polymer. The crosslinked network is formed by the ethylene polymer and BiTEMPS methacrylate in the presence of a free radical initiator to form a crosslinked ethylene polymer composition. The crosslinking is dynamic because the chains are allowed to move and exchange when the crosslinked ethylene polymer composition is subjected to a "reprocessing temperature," which is a temperature of 160°C to 230°C or 160°C to 200°C. At the reprocessing temperature, the disulfide bonds in the crosslinked ethylene polymer composition are broken to form a reprocessable ethylene polymer composition. The reprocessable ethylene composition is cooled to below the reprocessing temperature to form a re-crosslinked ethylene polymer composition.
[0102] The dynamic crosslinker BiTEMPS methacrylate enables cyclic "reprocessing" to make new polymer articles. When the crosslinked ethylene polymer composition is heated to the reprocessing temperature, the disulfide bonds are broken or otherwise cleaved, allowing the previously crosslinked ethylene polymer composition to flow at the reprocessing temperature, thereby forming a "reprocessable ethylene polymer composition". Heating to the reprocessing temperature enables chain scission and polymer chain flow, thereby allowing the ethylene composition to be easily reshaped. At the reprocessing temperature, the reprocessable ethylene polymer composition is no longer crosslinked, but is flowable, allowing the now flowable, reprocessable ethylene composition (with BiTEMPS methacrylate) to be shaped and / or manufactured into a new preform or article. When cooled to below the "reprocessing temperature", the disulfide bonds are formed again, the network is reestablished, and the re-crosslinked ethylene composition is formed in a new article configuration, returning to high viscosity (no flow at room temperature) and resistance to mechanical deformation indicating a crosslinked network. When the newly formed article of the reprocessable ethylene polymer composition is cooled to below the reprocessing temperature, the disulfide bonds in the reprocessable ethylene polymer composition are reestablished and the ethylene polymer (with BiTEMPS methacrylate) becomes a recrosslinked ethylene polymer composition in the shape of the newly manufactured article. Below the reprocessing temperature, the network disulfide bonds are stable and the recrosslinked ethylene polymer composition exhibits high viscosity and resistance to mechanical deformation indicative of the crosslinked network. This cycle of crosslinking / reprocessing / recrosslinking into a new article can be repeated.
[0103] Without being bound by a particular theory, the number of "reprocessing" cycles possible for the crosslinked ethylene compositions of the present invention can be determined by calculating the ratio of the melt viscosities of the crosslinked ethylene polymer composition before and after the reprocessing cycle (before competing thermal and oxidative permanent crosslinking occurs and prevents further reprocessing). For reprocessable, crosslinked ethylene polymer compositions, the ratio of the viscosity after reprocessing to the viscosity before reprocessing is from 0.5 to 5, or from 0.7 to 3, or from 0.9 to 2, or from 0.95 to 1.2.
[0104] Other metrics used to monitor the number of "reprocessing" cycles possible for the BiTEMPS methacrylate dynamic crosslinker before competing oxidative permanent crosslinking occurs include visual observation. The mechanically deformed formed film is heated to the reprocessing temperature and visually inspected to determine if the mechanically deformed film has healed to form a stable film.
[0105] In one embodiment, the method includes grinding the cross-linked article to form a ground material and heating the ground material to a reprocessing temperature of 180° C. to 199° C. The method includes forming the re-ground material into a reprocessable (polar) ethylene polymer composition at the reprocessing temperature, and forming the reprocessable (polar) ethylene polymer composition into a reprocessing preform at the reprocessing temperature. The method includes cooling the reprocessed preform to below the reprocessing temperature; and forming a reprocessed cross-linked article.
[0106] The reprocessed cross-linked article contains disulfide bonds formed from BiTEMPS methacrylate by the re-cross-linking reaction, and the disulfide bonds have the following structure 2.
[0107] Structure 2
[0108]
[0109] Suitable articles for reprocessing the (polar) ethylene polymer compositions (having bonds of Structure 2 formed from BiTEMPS methacrylate) include elastic films; elastic fibers; soft-touch items such as toothbrush handles and appliance handles; pads and profiles; adhesives (including hot melt adhesives and pressure sensitive adhesives); footwear (including soles and shoe insoles); automotive interior parts and profiles; foam articles (both open-cell and closed-cell foams); impact modifiers for other thermoplastic polymers such as high-density polyethylene, isotactic polypropylene or other olefin polymers; coated fabrics; hoses; pipes; weather stripping; lid linings; flooring; and combinations thereof.
[0110] In one embodiment, the method comprises heating the crosslinked article to a reprocessing temperature of 200°C to less than 250°C or 200°C to 230°C and forming the crosslinked article into a reprocessable (polar) ethylene polymer composition at the reprocessing temperature. The method comprises forming the reprocessable (polar) ethylene polymer composition into a reprocessed preform at the reprocessing temperature, cooling the reprocessed preform to below the reprocessing temperature, and forming a reprocessed thermoplastic article. The reprocessing temperature from 200°C to less than 250°C completely dissociates the disulfide bonds, thereby completely dissociating the bonds between the polymer chains in an irreversible manner. The result is a thermoplastic material.
[0111] 2. Materials
[0112] The materials used in the comparative samples (CS) and the inventive examples (IE) are provided in Table 1 below.
[0113] Table 1: Materials used and their properties
[0114]
[0115] 3. Formulation
[0116] Table 2. Formulations and methods for producing reactively grafted BiTEMPS compounds
[0117]
[0118] As indicated in Table 2 above, the grafted BiTEMPS polymers were prepared by one of the two methods described herein, extrusion and Haake mixing.
[0119] Xplore MC 40 Micro Extrusion
[0120] Specifically, for IE 5, change ENGAGE TM 8450, dicumyl peroxide, and BiTEMPS methacrylate were combined in the amounts shown in Table 2 and batch mixed in a Haake mixer at 100°C to form a crosslinkable / pre-grafted polymer composition. Prior to extrusion, the formulation was evaluated on an RPA at 160°C for 60 minutes to understand the reactivity characteristics of the composition. It is noteworthy that at this temperature (160°C), DCP was triggered to form the initiator BiTEMPS and ENGAGE TM 8450. These reactions are known to occur generally at temperatures above 140°C, as the decomposition temperature of DCP is reported to be 133°C to 143°C. Jiayu Lv et al. "Kinetic analysis and self-accelerating decomposition temperature (SADT) of dicumyl peroxide", Thermochimica Acta, Vol. 571, 2013, pp. 60-63. In addition, it is also known that reactivity increases with increasing temperature.
[0121] Figure 1 The RPA curve (torque versus viscosity) of IE5 at 160°C for 1 hour is provided. Figure 1 As can be seen in , when the compound temperature is maintained at 160 °C, the torque and viscosity increase, confirming that the grafting reaction is effectively initiated at temperatures above 160 °C.
[0122] The sample obtained by batch mixing was then further reactively extruded on an Xplore MC 40 micro-compounder ("MC 40"), and the curled strands were collected. For this process, 20 g of the batch mixed sample was processed on the MC 40. At a temperature of 200°C. The screw speed was initially set to 25 rpm. About 10 g of the sample was added to the MC 40 and allowed to melt about 30 / 3. Another 10 g of the sample was then added. The screw speed was increased to 50 rpm. The material was then recirculated in the micro-compounder for 5 minutes, at which time a stable torque reading was obtained. A single extrudate strand of about 4 mm in diameter was then extruded from the micro-compounder. The properties of the extruded material are reported in Table 3 below.
[0123] Table 3. Properties of crosslinked composition IE 5
[0124] <![CDATA[IE 5ENGAGE TM 8450 Graft]]> characteristic RPA S'(dNm) at 160℃, 60 minutes 1.68 RPAn*(Pa-s) at 0.1rad / s, 160℃ 947,253 RPA n*(Pa-s) at 300rad / s and 160℃ 1,222 RPAtanδ at 0.1rad / s and 160℃ 0.42 RPAn*(Pa-s) at 0.1rad / s, 230℃ 54,258 RPA n*(Pa-s) at 300rad / s and 230℃ 459 RPA tanδ at 0.1rad / s, 230℃ 1.31 Viscosity Temperature Reprocessing Ratio 17.5 Reprocessable yes
[0125] The viscosity temperature reprocessing ratio is defined as the ratio of n* at 0.1 rad / s, 160° C. to n* at 0.1 rad / s, 230° C. S′ at 160° C., 60 minutes and n* at 0.1 rad / s, 160° C. indicate that IE 5 has undergone a crosslinking reaction. The significant drop in n* at 0.1 rad / s, 230° C. (high viscosity temperature reprocessing ratio) indicates that the crosslinked composition can be reprocessed at this elevated temperature.
[0126] The extruded strands were collected on a Teflon sheet about 6 inches from the die exit and moved by hand to collect the curled strands, where the extrudate curled itself to form a joint, repeating the 3D loop extrusion and bonding process. The curled strands were allowed to cool to room temperature. The strength of the strand joints was evaluated by cutting a single bonded joint from the curled strands and evaluating it on an Instron test frame under uniaxial tension. The peak load of IE 5 was measured and reported in Table 4 below.
[0127] Table 4. IE 5Peak Load
[0128]
[0129] IE 5 had a measurable peel force, indicating that bonding did occur between the extruded strands and the article resembled a 3D ring material, and thus the reversibly crosslinked composition IE 5 composition could be used to form a 3D ring structure.
[0130] Haake TM Batch Mixing
[0131] Using Haake TMMixer Examples 6-7 were prepared in the following manner. This method is intended to simulate a reactive extrusion process, where the reactive ingredients (i.e., DCP and BiTEMPS) are added to the polymer melt at a temperature at which DCP can initiate the grafting / crosslinking reaction, followed by further mixing in a mixing or extrusion device. When the quantities required for reactive extrusion are not available, Haake TM Mixing studies to determine candidacy for reactive extrusion.
[0132] The polymer formulations for IE 6 to 7 are listed in Table 2. For each composition in Table 2, polymer pellets were mixed on an RSI RS5000 with a CAM blade, a RHEOMIX 600 (as a Haake TM Mixers from Polylabs TM The obtained) were melt blended in a batch mixer at 180°C for a total of 15 minutes. This allowed the HDPE polymer to melt completely. After this 15 minute period, DCP and BiTEMPS were added at 180°C over a period of 10 minutes.
[0133] like Figure 2 and Figure 3 As shown, it is clearly indicated that grafting / crosslinking occurs during the mixing step. A significant increase in mixing torque is observed after the addition of BiTEMPS and DCP at 180°C (approximately 600 seconds or 10 minutes).
[0134] Then after mixing for another 5 minutes, the reactively grafted polymer samples were taken from RSI RS5000, RHEOMIX600 (as Haake TM Mixers from Polylabs TM The obtained mixture was taken out from a batch mixer.
[0135] It was found that at temperatures greater than 230°C, side reaction materials were generated, turning the polymer dark brown and causing degradation of the polymer's physical properties. However, if the batch mixing temperature was below 150°C, no grafting occurred, and if the polymer blend temperature was high, torque was generated.
[0136] After removal from the batch mixer, IE 6 to 7 compression molded samples were formed at 180°C and 10 MPa molding pressure for 5 minutes and then quenched between cooling platens (15°C to 20°C) for 2 minutes. The properties of IE 6 and 7 are provided in Table 4 below.
[0137] Table 4. Characteristics of IE 6 and 7 and Comparative Samples (CS) 1 and 2
[0138]
[0139] 4. Preparation of Reprocessed Thermoplastic Articles (Method C)
[0140] After compression molding and cooling, IE 7 of Table 4 was reprocessed under conditions that allowed the reprocessing of thermoset materials into thermoplastic materials. Here, IE 7 compression molded polymer plaques were cut into strips and fed into a co-rotating twin-screw Xplore MC40 micro-compounder at 50 RPM and in a temperature range of 230° C. for six minutes. The polymer strands were then extruded from the outlet of the micro-compounder and rolled in a Teflon TM The coated material was collected and cooled on the surface of a stainless steel plate.
[0141] Due to the dissociative bonding between polymers, the viscosity (torque) is reduced and the sample can be successfully extruded in a continuous manner. At temperatures greater than 250°C, side reaction materials are produced, resulting in sample degradation, while temperatures below 200°C result in high torque strains that inhibit extrusion. Figure 4 A side-by-side comparison of compression molded IE7 and reprocessed IE7' is depicted (RPA curve of Example IE7' reprocessed at 200°C to 230°C).
[0142] Table 5 provides the following extrusion conditions for reprocessing IE 7:
[0143] Table 5. Extrusion of reprocessed IE 7
[0144]
[0145] like Figure 4 As can be seen in the thermosetting material, the thermosetting material becomes a thermoplastic material, which can be further manufactured into an article or formulated for subsequent applications. Non-limiting examples of suitable articles include elastic films; elastic fibers; soft-touch items such as toothbrush handles and utensil handles; pads and profiles; adhesives (including hot melt adhesives and pressure sensitive adhesives); footwear (including soles and shoe insoles); automotive interior parts and profiles; foam articles (both open-cell foam and closed-cell foam); impact modifiers for other thermoplastic polymers such as high-density polyethylene, isotactic polypropylene or other olefin polymers; coated fabrics; hoses; pipes; windbreaks; lid linings; flooring; and combinations thereof.
[0146] 5. Preparation of reprocessed thermosetting products (D)
[0147] Also provided herein is the reprocessability of IE 5 under the conditions under which thermosets are prepared. The extruded strands were reprocessed to form compression molded discs for compression set testing. The strands of IE 5 were cut into sheets and compression molded into 1.2 inch diameter, 0.5 inch thickness discs at 180°C for 15 minutes on a Carver molding machine with a model 4095, 60 ton, dual daylight opening size 12" x 12" heating / cooling platens, and a temperature range capability of 20°C to 260°C. Third, the compression set at 70°C was evaluated as reported in Table 6, which compares the reprocessed IE 5' with the ENGAGE TM 8450. As shown below, IE5' has a non-crosslinked ENGAGE TM 8450 Example similar compression set, demonstrating that the reversibly crosslinked composition retains similar physical properties at 70°C. TM Each compression set disc of 8450 and IE 5' was reprocessed by compression molding to form a new 1.2 inch diameter, 0.5 inch thick disc by compression molding at 180°C for 15 minutes. Each sample was then compressed at 125°C at 25% strain for 22 hours and then allowed to cool to room temperature. Figure ZZZ shows a photograph of a top view of each compression set disc after compression at 125°C at 25% strain for 22 hours. ENGAGE TM 8450 melts and deforms at 125°C because this is above the melting point of the sample and it is not cross-linked. Figure 5 As shown, IE 5′ all retained their shapes, demonstrating that the heat resistance of the cross-linked samples was improved.
[0148] Table 6 - Compression set
[0149] Compression set (22 hours, 70°C)% <![CDATA[ENGAGE TM 8450]]> 61 IE 5′ 67
[0150] It is particularly intended that the present disclosure is not limited to the embodiments and descriptions contained herein, but includes modifications of those embodiments including parts of the embodiments and combinations of elements of different embodiments as appear within the scope of the following claims.
Claims
1. A method, comprising: A crosslinkable polymer composition is provided, the crosslinkable polymer composition comprising: (i) a (polar) ethylene polymer, said (polar) ethylene polymer having a melting temperature Tm, (ii) a free radical initiator having a decomposition temperature T 分解 ,and (iii) 2,2,6,6-tetramethyl-4-piperidinyl methacrylate disulfide (BiTEMPS methacrylate); mixing the blend components in a mixing device at a temperature greater than or equal to the decomposition temperature of the peroxide; as well as BiTEMPS methacrylate grafted (polar) vinyl polymer (BiT-g-pPE) was formed.
2. The method according to claim 1, comprising forming a BiT-g-pPE comprising a bond having structure 3 3. The method according to any one of claims 1 to 2, wherein the mixing comprises (A) melt blending a (polar) ethylene-based polymer at a first temperature for a first process period; (B) adding the BiTEMPS methacrylate and a free radical initiator to the melt blended ethylene polymer of step (A) during a second process period to form a reaction mixture; (C) blending the reaction mixture at a second temperature for a third process period; and (D) Formation of the BiT-g-pPE.
4. The method of claim 3, wherein the free radical initiator is dicumyl peroxide and the second temperature is from 160°C to less than 180°C.
5. The method of any one of claims 1 to 4, comprising collecting the BiT-g-pPE as pellets, one or more bags, and a combination of pellets and one or more bags.
6. The method according to any one of claims 1 to 5, comprising heating the BiT-g-pPE to a crosslinking temperature of 180° C. to less than 199° C.; forming the BiT-g-pPE into a preform at the crosslinking temperature; cooling the preform to below the crosslinking temperature; as well as A cross-linked product is formed.
7. The method of claim 6, wherein the cross-linked article comprises (i) the (polar) vinyl polymer; and (ii) Bonds with structure 2 8. The method according to any one of claims 6 to 7, comprising: grinding the cross-linked article to form an abrasive material, heating the ground material to a reprocessing temperature of 180° C. to 199° C.; forming the regrind material into a reprocessable (polar) ethylene polymer composition at said reprocessing temperature; forming the reprocessable (polar) ethylene polymer composition into a reprocessable preform at the reprocessing temperature; cooling the reprocessed preform to below the reprocessing temperature; as well as A reprocessed cross-linked article is formed.
9. The method according to claim 6, comprising: heating the cross-linked article to a reprocessing temperature of 200° C. to less than 250° C.; forming the crosslinked article into a reprocessable (polar) ethylene polymer composition at the reprocessing temperature; forming the reprocessable ethylene polymer composition into a reprocessable preform at the reprocessing temperature; cooling the reprocessed preform to below the reprocessing temperature; as well as A reprocessed thermoplastic article is formed.